Protection of the Rights of Child Victims of Sexual Violence in the Koppatara Foundation, Malang Regency Perspective Maqāṣid al-Sharī'ah Jasser Auda - Mafruhatul Umamah; Mufidah Cholil; Fadil SJ (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2023)
Children who experience violence need to be protected and their rights fulfilled, because many losses have been suffered. Children's rights are contained in Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 on Child Protection. In fact, the low quality of child protection in Indonesia has drawn a lot of criticism regarding the scope of the implementation of children's rights which is carried out as a form of protection for child victims of sexual violence to ensure the survival of children which is part of human rights. This research is a type of empirical legal research with interviews and documentation techniques; The results show that the process of protecting child victims of sexual violence by the Koppatara Foundation is through receiving complaints, accompaniment, case handling, and case termination. And the implementation of fulfilling the rights of child victims of sexual violence according to maqāṣid al-syarī'ah Jasser Auda can be implemented through the implementation of effective fulfillment of children's rights which aims for the benefit of the child and prioritizes legal certainty and upholds the values of justice are based on the main objectives of the policy The Child Protection Act for the benefit of child victims of sexual violence.